ANALISIS STRATEGI PEMBINAAN TAHFIDZUL QUR’AN BAGI MAHASISWA DI PESANTREN TAHFIDZ BANI YUSUF KOTA MALANG - Anwar, Muhammad Rosihan; Mufidah, Nuril (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This research aims to 1. analyze the strategies and problems experienced by students in coaching tahfidzul quran at the Pesantren Tahfidz Bani Yusuf Merjosari Malang City, 2. Describe the results of tahfidzul quran coaching at the Pesantren Tahfidz Bani Yusuf Merjosari Malang City. This research was conducted on students at the Pesantren Tahfidz Bani Yusuf in 2022/2023. This research uses a qualitative method with a case study approach. Data collection techniques in this research used observation, interviews and documentation studies. The strategy for developing tahfidzul quran with mudarosah, namely reciting half a juz of Al-Quran verses by heart to a listening partner or friend with the aim of improving the quality of reading and memorizing the Koran , fashohah , namely reading the Koran together led by a guide in tartil for one page, tasmi is a test increasing the memorization of the Koran which is divided into six stages according to multiples of five juz. The model for implementing tasmi is by listening to students who have carried out tasmi according to the tasmi level for one sitting, mauidzotul hasanah is providing advice, direction and positive knowledge to students to increase enthusiasm and motivation in memorizing the Koran. The problems often experienced by students in the strategy of developing tahfidzul quran at the Pesantren Tahfidz Bani Yusuf originate from within the individual; not being able to manage time well, feeling lazy, lack of preparation, and lack of focus in coaching activities. Evaluation of the results of the development of tahfidzul quran training which was able to achieve the target of memorizing thirty juz as many as two people, students who had completed more than fifteen juz totaled sixteen students out of thirty seven students